On-the-job learning among CEOs in Malaysian private organizations - Sundram, Subhashini; Abdrahim, Nur Aira (Macrothink Institute, 2022)
This article aims to explore Chief Executive Officers’ (CEOs’) past experiences in shaping the learning process that occurred at the workplace. A theoretical framework for this study is anchored from the situated learning theory. The primary elements of the situated learning theory are communities of practice and legal peripheral participation, which these concepts were investigated among the CEOs of private organizations in Malaysia. The study is interpretive in nature, employing a qualitative research approach with in-depth interviews to gain in-depth insights on the topic. The findings are meant to capture empirical insights that broaden the framework for a better understanding of situated learning in a workplace context. According to the study, experiences gained from the roles and responsibilities in contexts of learning-in-practice increase awareness and knowledge. Understanding learning occurs as a result of social experiences that include ways of thinking, perceiving, problem-solving, and interacting, in addition to declarative and procedural knowledge.